Decision support in reforestation through the analysis of soil and mycorrhiza data - Kozlova Anastasia; Ashmarina Tatyana; Kukartsev Vladislav; Yagudaeva Natalya; Biryukova Tatiana (BIO Web of Conferences)
This study presents an analysis of key biological and ecological factors affecting the growth and survival of tree seedlings. The dataset used includes information on soil types, levels of mycorrhizal activity, biochemical compound content, light availability, and other environmental parameters. Special attention is given to the relationships between mycorrhizal symbioses (AMF, EMF), plant physiological characteristics, and environmental conditions. Correlation and cluster analysis methods were applied to the data, allowing for the identification of tree groups with similar characteristics and an assessment of the impact of various factors on their survival. The results emphasize the importance of microbial interactions and biochemical indicators, such as phenol and lignin content, in the adaptation of trees to stressful conditions. This data can be used for decision-making in reforestation, including optimizing planting conditions and selecting the most resilient tree species. The study also highlights the importance of managing the soil microbiome to enhance the effectiveness of forest ecosystem restoration.